Decision support system for determining lecturer scholarships for doctoral study using CBR (Case-based reasoning) method - Susilowati T.; Manickam P.; Devika G.; Shankar K.; Latifah; Muslihudin M.; Hashim W.; Huda M.; Korostelev A.A.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Selection of lecturers of Scholarship Recipients is the recognition of lecturers who actually and extraordinarily carry out tridharma activities of higher education that the results can be proud of and beneficial for the advancement of academic and institutional quality improvement. The selection of scholarship recipients at the STMIK Pringsewu is conducted annually. In the assessment process of scholarship recipients, STMIK appoints an assessment team to assess lecturer candidates. However, the assessment process is still done manually so that it takes a long time to process data. In addition, the assessment is still subjective and not relevant to the actual situation. Based on this, the Decision Making Planning of Determining the STMIK Pringsewu Lecturer Scholarship for Doctoral Study Using CBR (Case Based Reasoning) Method was established. Decision support systems built on the web using PHP and MySQL programming languages as databases. The decision-making method used is the Case Based Reasoning (CBR) method. This method is used to determine the weight value of each criterion, which is then carried out the ranking process to determine the best alternative from a number of alternatives. Tests conducted in this study are functional testing with the black box testing method. The test results indicate that the system can run well according to its function. BEIESP.